The beginner's goodbye : [a novel] - Tyler, Anne.; Heyborne, Kirby; Random House Audio Publishing; Books on Tape, Inc. (Westminster, Md. : Books on Tape, 2012)
"Explores how a middle-aged man, ripped apart by the death of his wife, is gradually restored by her frequent appearances--in their house, on the roadway, in the markets ... Only Dorothy's unexpected appearances from the dead help him to live in the moment and to find some peace"--Provided by publisher.
Compact disc.
Unabridged.
Subtitle from container.
Read by Kirby Heyborne.
Keywords: Middle-aged men -- Fiction; Wives -- Death -- Fiction; Bereavement -- Fiction; Psychological fiction; Audiobooks